2003
DOI: 10.1095/biolreprod.102.007336
|View full text |Cite
|
Sign up to set email alerts
|

Embryotrophic Factor-3 from Human Oviductal Cells Affects the Messenger RNA Expression of Mouse Blastocyst1

Abstract: Our previous results showed that embryotrophic factor-3 (ETF-3) from human oviductal cells increased the size and hatching rate of mouse blastocysts in vitro. The present study investigated the production of ETF-3 by an immortalized human oviductal cell line (OE-E6/E7) and the effects of ETF-3 on the mRNA expression of mouse embryos. The ETF-3 was purified from primary oviductal cell conditioned media using sequential liquid chromatographic systems, and antiserum against ETF-3 was raised. The ETF-3-supplemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…These techniques have been used successfully to identify differentially expressed genes from the oviduct [Lee et al, 2000 and preimplantation embryos [Natale et al, 2000;Lee et al, 2001Lee et al, , 2003Ponsuksili et al, 2002;Yao et al, 2003]. In combination with cDNA microarray, SSH has been used to compare the gene expression patterns between the ipsilateral and contralateral bovine oviduct in the post-ovulation period ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques have been used successfully to identify differentially expressed genes from the oviduct [Lee et al, 2000 and preimplantation embryos [Natale et al, 2000;Lee et al, 2001Lee et al, , 2003Ponsuksili et al, 2002;Yao et al, 2003]. In combination with cDNA microarray, SSH has been used to compare the gene expression patterns between the ipsilateral and contralateral bovine oviduct in the post-ovulation period ].…”
Section: Discussionmentioning
confidence: 99%
“…Conjointly, our laboratory first reported the purification of embryotrophic factor-3 (ETF-3) from human oviductal cells [Liu et al, 1995]. ETF-3 could enhance embryo development in vitro Lee et al, 2003] and it was subsequently identified as C3-like molecules. Mouse embryos incubated with C3b and/or iC3b have large size and higher hatching rate in vitro [Lee et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Mouse embryos were collected and cultured as described previously (21). Briefly, 6-8-week-old female mice were superovulated by intraperitoneal injection of 5 IU pregnant mare's serum gonadotropin (Sigma) followed by an injection of 5 IU hCG (Sigma) 46 h later.…”
Section: Preimplantation Embryo Culturementioning
confidence: 99%
“…The procedure for obtaining superovulated embryos was essentially the same as before (27). Mature ICR female mice (age, 6 -8 wk) were superovulated with 5 IU pregnant mare's serum gonadotropin (Sigma), followed by an injection of 5 IU of hCG (Sigma) 46 h later.…”
Section: Embryo Collection and Culturementioning
confidence: 99%
“…We previously demonstrated that oviductal cells affect the gene expression of developing embryos in vitro (26), partly via embryotrophic factor-3 (27). On the other hand, developing embryos have also altered gene expression in the oviduct (6,28).…”
mentioning
confidence: 99%